ELECTRON MICROSCOPIC CHARACTERIZATION OF THE DYNAMICS OF SCIATIC NERVE DAMAGE IN RATS WITH CISPLATIN- AND PACLITAXEL-INDUCED NEUROTOXICITY - Kulynych, H.B.; Herashchenko, S.B.; Pertsovych, V.M.; Ryziuk, M.D.; Oliinyk, I.Y.; Tiron, O.I. (World of Medicine and Biology, 2025)
Chemotherapy-induced peripheral neuropathy limits the efficacy of cisplatin and paclitaxel in cancer treatment. This study characterized ultrastructural changes in the rat sciatic nerve on days 14 and 28 post-administration using transmission electron microscopy. Adult male inbred rats (n=30/group) were divided into three groups: paclitaxel (2 mg/kg i.p., 4 injections every other day, total 8 mg/kg), cisplatin (2 mg/kg i.p., twice weekly for 4 weeks, total 16 mg/kg), and combined treatment (cisplatin 2 mg/kg i.p. at 37°C+paclitaxel 5 mg/kg i.v. weekly for 6 weeks; total cisplatin 12 mg/kg, paclitaxel 30 mg/kg). Nerve fragments were fixed in 2°% osmium tetroxide, embedded in Epon/Araldite, and examined at ×4800–×16000. Cisplatin induced more severe degeneration than paclitaxel, including myelin destruction, axonal degeneration, and neuroglio-vascular swelling. Damage progressed from day 14 to 28, revealing cumulative toxicity. Combined administration exerted synergistic effects, disrupting the entire neuro-glio-vascular unit. Endothelial dysfunction emerged as the primary trigger. These findings underscore the multifactorial nature of CIPN and the need for early neuroprotective interventions targeting vascular stability and mitochondrial homeostasis. Basement membrane thickness increased from 158±19 nm (day 14, paclitaxel group) to 268±31 nm on day 28 in the combined treatment group.
Keywords: chemotherapy-induced peripheral neuropathy; cisplatin; paclitaxel; sciatic nerve; ultrastructure; electron microscopy; rats